USE OF ATLAS.TI SOFTWARE AS A METHODOLOGICAL RESOURCE IN THE STRUCTURING OF DATA IN QUALITATIVE STUDIES - Ribeiro, Gerusa; Alves, Caroline Scalabrin de Oliveira; de Mello, Diego Saraiva; Piva, Izabel Cristina Dell’Antônio; Marjory, Andressa; Misiak, Marciele; Huhn, Andréa; de Medeiros, Caroline (Seven Editora, 2026)
Use of ATLAS.ti Software as a Methodological Resource in the Structuring of Data in Qualitative Studies” presents the practical experience of faculty members and students from the Professional Master’s Program in Radiological Protection at the Federal Institute of Santa Catarina in the use of ATLAS.ti software to support qualitative analyses. The central objective is to demonstrate how the tool contributes to methodological rigor, the organization of large volumes of data, and the enhancement of research quality in the field of radiological protection. The study describes the software usage process, including installation, project creation, document import, code development, citation generation, network creation, and report export. ATLAS.ti is presented as an essential technology for contemporary qualitative research, especially in interdisciplinary health contexts. Its use facilitates data categorization, occurrence analysis, visualization of conceptual relationships, and analytical traceability, while maintaining fidelity to the theoretical frameworks defined by the researcher. The article highlights tools such as the document manager, code groups, Sankey diagrams, analytical memos, and networks, which expand the understanding of phenomena investigated in radiological protection and related areas. In addition to presenting practical examples from dissertations that used the software, the article discusses limitations, such as the risk of excessive and mechanized data segmentation, emphasizing that critical interpretation remains the researcher’s responsibility. It concludes that ATLAS.ti is an effective, accessible tool aligned with the scientific rigor required in qualitative research, contributing to the advancement of radiological protection and patient safety. DOI: https://doi.org/10.56238/sevened2026.008-076